2018
DOI: 10.1108/gm-06-2017-0076
|View full text |Cite
|
Sign up to set email alerts
|

Sponsorship and social identity in advancement of women leaders in South Africa

Abstract: Purpose: In South Africa women in senior management positions experience social identity dilemmas, necessitating more research into this domain. While research has been conducted into coaching and mentoring of these women, limited scholarly attention has been paid to sponsorship. This paper thus explored the social identity of women at senior management levels as well as sponsorship as a proposed mechanism to develop talented women.Design/methodology/ approach: This qualitative research included two studies us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…From the standpoint of social exchange, the reciprocal relationship between leaders (mentors) and mentees can boost members' self-efficacy and creativity in performing uncertain and risky tasks (Liao, Liu, & Loi, 2010). In the mentorship process, women emphasise the relational aspects of social exchange (Scheepers, Douman, & Moodley, 2018). The latter study also identified social exchange theory as a critical driver of women's talent development in South African businesses.…”
Section: Mentorship Role Models and Social Networkingmentioning
confidence: 94%
“…From the standpoint of social exchange, the reciprocal relationship between leaders (mentors) and mentees can boost members' self-efficacy and creativity in performing uncertain and risky tasks (Liao, Liu, & Loi, 2010). In the mentorship process, women emphasise the relational aspects of social exchange (Scheepers, Douman, & Moodley, 2018). The latter study also identified social exchange theory as a critical driver of women's talent development in South African businesses.…”
Section: Mentorship Role Models and Social Networkingmentioning
confidence: 94%
“…Ibarra et al (2010) found that men and women benefit differently from close mentorships. In the case of women, mentors focus on coaching and advising while men receive additional sponsorship in the form of a promotion and negotiation on their behalf (Ibarra et al , 2010; Scheepers et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…pay, promotion, training and wellbeing), biases and resistance/sabotage by male colleagues should be managed (Zhong et al, 2018). According to Scheepers et al (2018), sponsorships should be considered as a strategy to advance talent management. Sponsorships involve a powerful, influential person pledging public support to an individual groomed for a leadership position.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Although the number of women entering the workforce has been continuously increasing, only a small number of them manage to advance to management levels. According to Scheepers, Douman and Moodley (2018), in South Africa, women occupy only 23% of positions involved in making economic decisions and only 4% of Chief Executive Officer positions. These statistics are only symptoms of a larger underlying disease where men are considered more worthy and valuable than women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation